2016
DOI: 10.1371/journal.pone.0155756
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Ocean Colour Chlorophyll Trends

Abstract: In being at the base of the marine food web, phytoplankton is particularly important for marine ecosystem functioning (e.g., biodiversity). Strong anthropization, over-exploitation of natural resources, and climate change affect the natural amount of phytoplankton and, therefore, represent a continuous threat to the biodiversity in marine waters. In particular, a concerning risks for coastal waters is the increase in nutrient inputs of terrestrial/anthropogenic origin that can lead to undesirable modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 51 publications
10
88
0
Order By: Relevance
“…The flow of the Rhone, for instance, was very high in the early 1980s, at its lowest in the first years of the 21st c. and increasing again in the current decade, while the Ebro River flow has been decreasing steadily for the past 4 decades (Cozzi, Ibáñez, Lazar, Raimbault, & Giani, ). The variations in river flow are accompanied in all cases by a decrease in the nutrient load (Cozzi et al, ), which might explain the observed decrease in chlorophyll a concentration in the Gulf of Lions and NE Spain in the last two decades (Colella, Falcini, Rinaldi, Sammartino, & Santoleri, ).…”
Section: Methodsmentioning
confidence: 99%
“…The flow of the Rhone, for instance, was very high in the early 1980s, at its lowest in the first years of the 21st c. and increasing again in the current decade, while the Ebro River flow has been decreasing steadily for the past 4 decades (Cozzi, Ibáñez, Lazar, Raimbault, & Giani, ). The variations in river flow are accompanied in all cases by a decrease in the nutrient load (Cozzi et al, ), which might explain the observed decrease in chlorophyll a concentration in the Gulf of Lions and NE Spain in the last two decades (Colella, Falcini, Rinaldi, Sammartino, & Santoleri, ).…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that our approach is highly suitable at basin scale and in selected sub-regions. This new dataset for PFT could be an efficient tool for recording and understanding the response of the marine ecosystem to human pressures and thus for detecting eutrophication in the Mediterranean Sea (Vantrepotte and Mélin, 2010;Colella et al, 2016).…”
Section: Spatio-temporal Patterns At the Sub-regional Scalementioning
confidence: 99%
“…To stress and conform these findings we pursue a satellite trend analysis over the whole Alboran Sea, by applying the Mann-Kendall test and the Sens's method for trend estimation to the Chl concentration deseasonalized monthly time series, as obtained from the X-11 technique [52]. The analysis confirmed the negative Chl-a trend from 2011 to 2014, which follows a positive trend from 2003 to 2011 (Figure 9).…”
Section: Discussionmentioning
confidence: 76%